Mood of Persuasion in The Articles Just Terror Tactics Issued In The Rumiyah Magazine - Maisarah, Maisarah; Fanani, Achmad (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2021)
This research was to reveal the mood types of the clauses and the persuasion strategies applied in two texts in Rumiyah magazine. A discourse analysis was applied with the Hallidayan Systemic Functional Linguistics theory as the basis of analysis. The results showed that the texts are dominated by the declarative mood that functions as indirect directives and statements of opinion. The applied types of mood indicate that the author takes a position as the bearer of information. In the analytical part of the texts, the disclaimer technique is used to assure the readers that committing a terror is easy. In the hortatory part of the texts, the technique of suggestion is used by providing recommendations to the readers of how to do a terror operation. However, some clauses containing augmentation reflect the expertise technique of persuasion.